2010
DOI: 10.1074/jbc.m110.157396
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Overexpression of a Constitutively Active Form of Liver Glycogen Synthase Improves Glucose Homeostasis

Abstract: In this study, we tested the efficacy of increasing liver glycogen synthase to improve blood glucose homeostasis. The overexpression of wild-type liver glycogen synthase in rats had no effect on blood glucose homeostasis in either the fed or the fasted state. In contrast, the expression of a constitutively active mutant form of the enzyme caused a significant lowering of blood glucose in the former but not the latter state. Moreover, it markedly enhanced the clearance of blood glucose when fasted rats were cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…This mode of regulation of GYS2 is complex, as it can be phosphorylated by PKA, PKC isoforms, AMPK, glycogen synthase kinase 3 (GSK3) and possibly other kinases 151 . However, site-directed mutagenesis studies indicate that the most important phosphorylation site for GYS2 activity is Ser7, which is a substrate of AMPK and PKA 152,153 ; mice with adenoviral overexpression of GYS2 with a Ser7Ala mutation displayed increased levels of liver glycogen under both fasting and fed conditions 154 . These mice had markedly improved glucose tolerance and lower plasma levels of glucose in the fed state but not in the fasted state, which highlights the crucial role of hepatic glycogen synthesis in postprandial glucose disposal 154 .…”
Section: Control Of Hepatic Glycogen Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…This mode of regulation of GYS2 is complex, as it can be phosphorylated by PKA, PKC isoforms, AMPK, glycogen synthase kinase 3 (GSK3) and possibly other kinases 151 . However, site-directed mutagenesis studies indicate that the most important phosphorylation site for GYS2 activity is Ser7, which is a substrate of AMPK and PKA 152,153 ; mice with adenoviral overexpression of GYS2 with a Ser7Ala mutation displayed increased levels of liver glycogen under both fasting and fed conditions 154 . These mice had markedly improved glucose tolerance and lower plasma levels of glucose in the fed state but not in the fasted state, which highlights the crucial role of hepatic glycogen synthesis in postprandial glucose disposal 154 .…”
Section: Control Of Hepatic Glycogen Metabolismmentioning
confidence: 99%
“…However, site-directed mutagenesis studies indicate that the most important phosphorylation site for GYS2 activity is Ser7, which is a substrate of AMPK and PKA 152,153 ; mice with adenoviral overexpression of GYS2 with a Ser7Ala mutation displayed increased levels of liver glycogen under both fasting and fed conditions 154 . These mice had markedly improved glucose tolerance and lower plasma levels of glucose in the fed state but not in the fasted state, which highlights the crucial role of hepatic glycogen synthesis in postprandial glucose disposal 154 . Insulin, which is essential for hepatic glycogen synthase flux in vivo 10 , was long thought to act through the AKT-dependent inhibition of GSK3, which would favour the dephosphorylation of GYS2 (REF.…”
Section: Control Of Hepatic Glycogen Metabolismmentioning
confidence: 99%
“…Tissue preparation, RNA extraction, RT-PCR, and quantitative real-time PCR analyses were performed as described (23). The following TaqMan primer/probe sets (Applied Biosystems, Madrid, Spain) were used for quantitative RT-PCR: PTG (Mm01204084_m1), Hprt (Mm00446968_m1), pyruvate kinase (Pklr) (Mm00443090_m1), fatty acid synthase (Fasn) (Mm00662319_m1), acetyl CoA carboxylase (Acc1a) (Mm01304257_m1), SREBP1 (Mm00550338_m1), peroxisome proliferator-activated receptor (…”
Section: Rna Preparations and Quantitative Rt-pcrmentioning
confidence: 99%
“…In our study, melatonin administration recovered the expression of LGS in smoking rats (Figure ). Previous studies also showed that the overproduction of LGS in rats was an effective method for improving glucose tolerance, owing to its capacity to enhance glucose storage . Furthermore, the increased activity of LGS potentially enhances insulin sensitivity in the liver, which may explain the insulin‐sensitizing effect of melatonin in smoking rats.…”
Section: Discussionmentioning
confidence: 99%
“…As a key enzyme in glycogenesis, liver glycogen synthase (LGS), converts glucose into glycogen. The enzyme combines excess glucose into a polymeric chain for storage as glycogen . Therefore, we want to analyze which effects of hepatic glycogen accumulation and the expression of LGS play in the smoking.…”
Section: Introductionmentioning
confidence: 99%